Pengaruh Pola Asuh Terhadap Percaya Diri dan Prestasi Belajar Anak Desmigratif (Desa Migra Inovatif) Pati - Hidayati, Richma; Hidayah, Nur; Ramli, M. (Buletin Konseling Inovatif, 2021)
This study investigates the empirical findings on the parenting effects on innovative migrant village children's confidence and academic achievement in Pati. This quasi-experimental research uses a non-equivalent control group design with a 2x2 factorial version. Its subjects were 75 children of Indonesian Migrant workers. The test and non-test data were obtained and analyzed using Manova statistics. Generally, the research results confirm that parenting carries substantial effects on children's confidence and academic achievement.